Can you beat Churchill? : teaching history through simulations - Barnhart, Michael A., 1951- (Cornell University Press, 2021)
"Can You Beat Churchill? reveals the elixir for student engagement in the humanities disciplines. So what is this elixir? It has various names: participatory history, reactive history, role-immersion history. As all these terms imply, it is a way to get students to experience the past by entering it. Michael A. Barnhart shares his own experience to explain how his simulation works and, as vitally, why he designed it as it is today. In so doing, he takes his readers on a tour behind the curtain, so that they too might create something for their own course."--